2022
DOI: 10.1111/hepr.13852
|View full text |Cite
|
Sign up to set email alerts
|

Significance of ramucirumab following atezolizumab plus bevacizumab therapy for hepatocellular carcinoma using real‐world data

Abstract: Aim Few studies have reported the efficacy and safety of ramucirumab (RAM) after atezolizumab plus bevacizumab (Atezo/Beva) treatment and the overall associated outcomes. Thus, we aimed to evaluate the therapeutic effects and safety of RAM post‐treatment with Atezo/Beva. Methods This retrospective study enrolled 46 patients with unresectable hepatocellular carcinoma who were treated with RAM. The patients were classified into the RAM administered following Atezo/Beva failure (n = 12) or RAM administered follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A previous study noted that programmed cell death protein 1 blockade continued to provide inhibition in lymphocytes for a long period after finishing treatment [26], while basic research findings indicated that addition of the anti-vascular endothelial growth factor receptor (VEGFR)-2 antibody to ICI can potentially provide synergistic effects [27]. Furthermore, Shimose reported that the therapeutic effect of VEGFR-2 monoclonal antibody ramucirumab was increased in patients with Atez/Bev failure as compared to those of another MTA (mPFS: 3.9 vs. 1.9 months, p = 0.047) [28]. Thus, a pseudo-combination effect of MTA therapies might be expected following progression in patients given immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study noted that programmed cell death protein 1 blockade continued to provide inhibition in lymphocytes for a long period after finishing treatment [26], while basic research findings indicated that addition of the anti-vascular endothelial growth factor receptor (VEGFR)-2 antibody to ICI can potentially provide synergistic effects [27]. Furthermore, Shimose reported that the therapeutic effect of VEGFR-2 monoclonal antibody ramucirumab was increased in patients with Atez/Bev failure as compared to those of another MTA (mPFS: 3.9 vs. 1.9 months, p = 0.047) [28]. Thus, a pseudo-combination effect of MTA therapies might be expected following progression in patients given immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by adequately monitoring patients and matching the dose of lenvatinib, AEs could be safely managed, and the results suggest that this enables even advanced HCC patients with symptoms of anorexia or fatigue to experience a normal level of benefits from lenvatinib treatment. The desired effects of ICIs (e.g., atezolizumab or bevacizumab) on the immune system tend to be long-lasting, and, after treatment of HCC patients with ICIs, favorable effects have been reported for the use of the anti-VEGFR-2 monoclonal antibody ramucirumab or the multi-kinase inhibitor cabozantinib (an MTA) as second-line therapies (34)(35)(36). Our results are in line with these findings, and support the possibility of a favorable pseudo-combination therapy effect when administering agents that inhibit other cellular signaling pathways to patients who earlier received immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no significant evidence for second-line treatment in patients in whom atezolizumab plus bevacizumab has failed, ramucirumab (53,54) and lenvatinib (55) have shown promising results as second-line treatments. Cabozantinib may have beneficial effects in patients who have received one or two prior systemic anticancer therapies for advanced HCC with subsequent radiographic progression (56).…”
Section: B-5 Systemic Therapiesmentioning
confidence: 99%